Peran Guru Dalam Mengembangkan Kemampuan Pada Anak ADHD Hiperaktif Implusif Pada Anak Usia 5 Tahun - Cahya, Galuh; Izza, Hanesya; Safinah, Dinara; Fardasyah, Zida; Razhika, Dania; Qurrotu, Clarissa; Dwi, Ajeng; Mukhoiyaroh, Mukhoiyaroh (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Early childhood education (ECCE) involves instruction with a focus on maturing each child's individual personality while also supporting the child's general development. Between two and four percent of school-age children in Indonesia are ADHD sufferers. A youngster with ADHD behaves differently from a typical child in a distinctive way. difficulties concentrating, hyperactivity, or attention deficit disorder. Because it affects both hyperactivity and attention deficit disorder, early childhood hyperactivity is a severe issue. The prevalence of attention deficit disorder and hyperactivity in children is rising these days